Visual Impairment in the South Indian State of Andhra Pradesh: Andhra Pradesh - Rapid Assessment of Visual Impairment (AP-RAVI) Project - Marmamula, Srinivas; Narsaiah, Saggam; Shekhar, Konegari; Khanna, Rohit C.; Rao, Gullapalli N. (PloS one, 2013)
To assess the prevalence and causes of visual impairment in urban and rural population aged ≥ 40 years in the South India state of Andhra Pradesh. A population based cross-sectional study was conducted in which 7800 subjects were sampled from two rural and an urban locations. Visual Acuity (VA) was assessed using a tumbling E chart and eye examinations were performed by trained vision technicians. A questionnaire was used to collect personal and demographic information and previous consultation to eye care providers. Blindness and moderate Visual Impairment (VI) was defined as presenting VA <6/60 and <6/18 to 6/60 in the better eye respectively. VI included blindness and moderate VI. Of the 7800 subjects enumerated, 7378 (94.6%) were examined. Among those examined, 46.4% were male and 61.8% of them had no education. The mean age of those examined (51.7 years; standard deviation 10.9 years) was similar to those not examined (52.8 years; standard deviation 9.9 years) (p=0.048). Age and gender adjusted prevalence of VI was 14.3% (95% CI: 13.5-15.0). Refractive errors were the leading cause of VI accounting for 47.6% of all VI followed by cataract (43.7%). Together, they contributed to over 91.3% of the total VI. With multiple logistic regression, the odds of having VI increased significantly with increasing age. Those respondents who had no education were twice (95% CI: 1.7-2.5) more likely to have VI compared to those who were educated. VI was associated with rural residence (OR: 1.3; 95% CI: 1.1-1.6). The association between VI and gender was not statistically significant. The visual impairment remains a public health challenge in Andhra Pradesh, most of which can be addressed with relatively straight forward interventions like cataract surgery and spectacles. The eye care services need to be streamlined to address this challenge.